Neuromechanical Considerations for Postconcussion Musculoskeletal Injury Risk Management. Issue 6 (November 2017) - Wilkerson, Gary B.; Grooms, Dustin R.; Acocello, Shellie N.
Abstract : Recent epidemiological studies have documented increased susceptibility to musculoskeletal injury after sport-related concussion, which raises questions about the adequacy of current clinical practices to ensure safe return to sport. A growing body of evidence derived from advanced neuroimaging and neurological assessment methods strongly suggests that mild traumatic brain injury has long-lasting adverse effects that persist beyond resolution of clinical symptoms. Plausible interrelationships among postconcussion changes in brain structure and function support the rationale for specific methods of clinical assessment and training to target the interaction of cognitive and motor function for reduction of musculoskeletal injury risk after concussion. The findings of preliminary clinical studies are presented to support suggested strategies for reduction of postconcussion musculoskeletal injury risk, and to identify novel approaches that we consider worthy areas for further research. Abstract : Currently used neurocognitive tests appear to have limited value for assessment of the extent to which normal brain function has been recovered after concussion. Subtle deficiencies that persist beyond resolution of overt clinical symptoms appear to be responsible for increased musculoskeletal injury incidence after return to sport participation. Neuromechanical responsiveness to rapidly changing conditions in a competitive sport environment may be best assessed by a battery of dual-task tests that impose some combination of concurrent visual, cognitive, and motor demands. Although very little definitive evidence is currently available to guide training for optimization of neuromechanical responsiveness, dual-task activities of progressively increasing difficulty have been found to improve peripheral visual awareness, visual-motor reaction time, and postural balance. Such training activities appear to offer the potential for reduction of musculoskeletal injury risk, which needs to be confirmed or refuted by further research.